PENGARUH MUTU PELAYANAN DAN NILAI PELANGGAN TERHADAP LOYALITAS PELANGGAN - Aspizain Chaniago (POLITEKNIK LP3I JAKARTA, 2012)
Through quantitative analysis approach to correlation analysi sof service quality and customer valueto customer loyalty, conducted the data collection questionnaire and the analyzed with SPSS so we get the conclusion there is a significant influence ofservice qualityon custome rloyalty, high quality of service that will deliver high-impact customer loyalty. There significant influence of customer value on customer loyalty, high customer value will impact thigh customer loyalty. Studies have shown the influence of service quality on customer loyalty and customer value effect on customer loyalty to fit empirical results with previous studies.Kata Kunci :Mutu Pelayanan, Nilai Pelanggan, Loyalitas Pelanggan.